Diagnostic methods and treatment options for focal cortical dysplasia. (5th October 2015) - Guerrini, Renzo; Duchowny, Michael; Jayakar, Prasanna; Krsek, Pavel; Kahane, Philippe; Tassi, Laura; Melani, Federico; Polster, Tilman; Andre, Véronique M.; Cepeda, Carlos; Krueger, Darcy A.; Cross, J. Helen; et al.
Summary: Our inability to adequately treat many patients with refractory epilepsy caused by focal cortical dysplasia (FCD), surgical inaccessibility and failures are significant clinical drawbacks. The targeting of physiologic features of epileptogenesis in FCD and colocalizing functionality has enhanced completeness of surgical resection, the main determinant of outcome. Electroencephalography (EEG)–functional magnetic resonance imaging (fMRI) and magnetoencephalography are helpful in guiding electrode implantation and surgical treatment, and high‐frequency oscillations help defining the extent of the epileptogenic dysplasia. Ultra high‐field MRI has a role in understanding the laminar organization of the cortex, and fluorodeoxyglucose–positron emission tomography (FDG‐PET) is highly sensitive for detecting FCD in MRI‐negative cases. Multimodal imaging is clinically valuable, either by improving the rate of postoperative seizure freedom or by reducing postoperative deficits. However, there is no level 1 evidence that it improves outcomes. Proof for a specific effect of antiepileptic drugs (AEDs) in FCD is lacking. Pathogenic mutations recently described in mammalian target of rapamycin (mTOR) genes in FCD have yielded important insights into novel treatment options with mTOR inhibitors, which might represent an example of personalized treatment of epilepsy based on the known mechanisms of disease. The ketogenic diet (KD) has been demonstrated to be particularly effective in children with epilepsy caused by structural abnormalities, especially FCD. It attenuates epigenetic chromatin modifications, a master regulator for gene expression and functional adaptation of the cell, thereby modifying disease progression. This could imply lasting benefit of dietary manipulation. Neurostimulation techniques have produced variable clinical outcomes in FCD. In widespread dysplasias, vagus nerve stimulation (VNS) has achieved responder rates >50%; however, the efficacy of noninvasive cranial nerve stimulation modalities such as transcutaneous VNS (tVNS) and noninvasive (nVNS) requires further study. Although review of current strategies underscores the serious shortcomings of treatment‐resistant cases, initial evidence from novel approaches suggests that future success is possible.